Legal Protection of Foreign Investments under the Rules of International Law: A Comparative Study between the United Arab Emirates and Jordan - Najdawi, Mohamed Hadi Al; Raafat, Raghda (Journal of Posthumanism, 2025)
The research aims to compare the laws of the United Arab Emirates and Jordan and determine whether they are in compliance with international standards in order to assess the legal frameworks for safeguarding foreign investments in both nations. Additionally, it aims to determine the advantages and disadvantages of national legislation as well as how they affect the ability to draw in international investment. Additionally, it seeks to offer suggestions for improving legal protection and guaranteeing a more stable investment climate. The study is significant because it shows how effective national laws are in safeguarding foreign assets, which helps to enhance the two nations’ investment-friendly legal environments. Determining the legal changes necessary to draw in foreign capital and promote economic growth is also beneficial. Furthermore, governments, decision-makers, and investors can use the information as a legal reference when creating investment policy. The methodology used in this study is the survey methodology, which relies on collecting data from a sample representing the study community using a questionnaire. The study’s most significant findings are that, while Jordan’s legal system still need revisions to make it more appealing to foreign investors, the United Arab Emirates offers a more stable legal environment with contemporary rules and regulations that adhere to international norms. In order to improve legal stability and promote openness in investment transactions, the study also suggested that Jordan’s investment laws be updated to meet worldwide standards.